2021
DOI: 10.3390/ijms222010983
|View full text |Cite
|
Sign up to set email alerts
|

Hijacking Sexual Immuno-Privilege in GBM—An Immuno-Evasion Strategy

Abstract: Regulatory T-cells (Tregs) are immunosuppressive T-cells, which arrest immune responses to ‘Self’ tissues. Some immunosuppressive Tregs that recognize seminal epitopes suppress immune responses to the proteins in semen, in both men and women. We postulated that GBMs express reproductive-associated proteins to manipulate reproductive Tregs and to gain immune privilege. We analyzed four GBM transcriptome databases representing ≈900 tumors for hypoxia-responsive Tregs, steroidogenic pathways, and sperm/testicular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 168 publications
(237 reference statements)
1
18
0
Order By: Relevance
“…This abolishes the gender effect on the action of this receptor. The synthesis of androgens by GBM cells itself may be associated with the migration of RORC-Treg cells (regulatory T cells with the related orphan receptor C) into the tumor niche and the formation of an immunosuppressive microenvironment, further facilitating tumor growth [ 36 ]. The hypoxia present in the GBM tumor further enhances the transformation of T Th17 into RORC-Treg [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This abolishes the gender effect on the action of this receptor. The synthesis of androgens by GBM cells itself may be associated with the migration of RORC-Treg cells (regulatory T cells with the related orphan receptor C) into the tumor niche and the formation of an immunosuppressive microenvironment, further facilitating tumor growth [ 36 ]. The hypoxia present in the GBM tumor further enhances the transformation of T Th17 into RORC-Treg [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The supportive influence of microglial cells on glioma growth is now established beyond doubt and can even be reproduced in a xenograft model [ 52 ]. Interestingly, microglia seem to exert a sex-specific influence in the TME [ 53 ] which may help to explain why GBM is more common and aggressive in male patients. In fact, the hijacking of sexual immune privilege by GBM has been identified as an immune evasion strategy of the glioma [ 53 , 54 , 55 ].…”
Section: Heterogeneity Of Cells In Tmementioning
confidence: 99%
“…Interestingly, microglia seem to exert a sex-specific influence in the TME [ 53 ] which may help to explain why GBM is more common and aggressive in male patients. In fact, the hijacking of sexual immune privilege by GBM has been identified as an immune evasion strategy of the glioma [ 53 , 54 , 55 ].…”
Section: Heterogeneity Of Cells In Tmementioning
confidence: 99%
“…Our prior analysis of glioblastoma (GBM) transcriptomes highlighted the expression of genes involved in the syntheses of estrogens and androgens. These steroids create immunosuppressive niches and allow GBMs to express reproduction-related proteins that evoke immune privilege [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Control of PGD 2 /PGF 2 ratios: Since hypoxia/hypoxia-inducible factor (HIF) signaling downregulates AKR1C3 expression, PGD 2 /F 2 ratios should correlate with hypoxic/normoxic conditions [ 49 , 50 ]. Estrogen/estrogen receptor-β signaling elevates AKR1C3 expression, and it has been previously shown that estrogenic tumors are heavily infiltrated by M2-polarized microglia and macrophages [ 1 , 31 ]. Estrogen is known to elevate CCL18 secretion in M2 macrophages [ 51 ], but it downregulates the expression of complement components, including C3, in normal brain tissue [ 52 ].…”
Section: Introductionmentioning
confidence: 99%